2012
DOI: 10.1130/ges00770.1
|View full text |Cite
|
Sign up to set email alerts
|

Middle Miocene to early Pliocene oblique extension in the southern Gulf of California

Abstract: A multichannel seismic (MCS) experiment spanning 600 km across the Alarcón Rise and its conjugate rifted margins in the southern Gulf of California (western North America) provides insight into the spatial and temporal evolution of extension between Baja California and the mainland (Mexico). Stratigraphic analysis of multiple rift basins within the Alarcón spreading corridor indicates an initial stage of oblique extension starting ca. 14-12 Ma. This initial phase of extension was characterized by the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 56 publications
3
70
0
8
Order By: Relevance
“…3), coincident with the onset of rifting of the GoC at this time (e.g. Stock & Hodges 1989;Umhoefer et al 2001;Sutherland et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), coincident with the onset of rifting of the GoC at this time (e.g. Stock & Hodges 1989;Umhoefer et al 2001;Sutherland et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The second outcome is that biostratigraphical studies, particularly from the offshore basins are recording a more protracted history of rift basin subsidence and sediment accumulation in the GoC and that marine sedimentation began at least in the middle Miocene (c. 12 Ma; Helenes 2012; cf. Sutherland et al 2012). This would require unrealistically rapid crustal thinning and subsidence if all extension began c. 12 Ma.…”
Section: Discussionmentioning
confidence: 99%
“…14-12.5 Ma); i.e., extension occurred when subduction was still ongoing. However, after the infl uential work of Stock and Hodges (1989), most (e.g., Henry andArandaGómez, 1992, 2000;Umhoefer et al, 2001;Umhoefer, 2011;Fletcher et al, 2007;Lizarralde et al, 2007;Seiler et al, 2011;Sutherland et al, 2012;Miller and Lizarralde, 2013) assumed that extension in the Gulf of California region began only at the end of Middle Miocene time, when subduction ended and the transfer of Baja California to the Pacifi c plate began. In the past two decades workers have debated the onset of oblique rifting in the Gulf of California (e.g., Stock and Hodges, 1989;Gans, 1997;Oskin and Stock, 2003;Fletcher et al, 2007;Miller and Lizarralde, 2013), but a general consensus has existed where gulf opening was fundamentally a post-subduction event, controlled by the highly oblique, northwestward motion of Baja California that was able to rift the continental lithosphere in ~6-10 m.y.…”
Section: Introductionmentioning
confidence: 99%
“…Henry and Fredrikson (1987) and Henry (1989) suggested that extension in Sinaloa adjacent to the Gulf of California might be as old as Late Oligocene based on the age of a few dated north-northwest-trending dikes in the region, and a maximum age of 17 Ma was reported for extensional faulting. Subsequently, it has been assumed that the GEP in this area developed after the end of the Middle Miocene (Henry and Aranda Gómez, 2000;Ferrari et al, 2002;Aranda Gómez et al, 2003;Sutherland et al, 2012), although geologic studies and radiometric ages to support this interpretation were restricted to a few locations.…”
Section: Introductionmentioning
confidence: 99%
“…12 million years, Baja has been dextrally transported at least 300 km north and west of its origin (Fig. 11A: Umhoefer 2011;Sutherland et al 2012;Bennett et al 2013; also see Bryan et al 2014), while the Gulf of California evolved on top of the previous and deceased arc system (Fig. 11A;Umhoefer 2011;Bennett et al 2013).…”
Section: An Alternative Model: Terrane Translationmentioning
confidence: 99%